Psychological Safety, Organizational Support, and Employee Well-being: The Moderating Role of Engagement - Raden Hasan; Hilda Yuliastuti; Lesna Purnawan; Caesar Rismanto; Febri Sari Siahaan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines how psychological safety and perceived organizational support influence employee well-being, while assessing employee engagement as a moderating variable in the manufacturing sector. Employee well-being has become an important concern for manufacturing organizations because employees often face production pressure, repetitive work routines, and demanding operational targets. A quantitative research design with a cross-sectional survey approach was employed. Data were collected from 150 manufacturing employees who had worked in their organizations for at least one year. Respondents were selected using purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 4. The measurement model confirmed adequate reliability, convergent validity, and discriminant validity, with all constructs meeting the recommended thresholds. The structural model demonstrated strong explanatory power, with an R-square value of 0.813 for employee well-being and a Q-square value of 0.536, indicating strong predictive relevance. The results show that psychological safety has a positive and significant effect on employee well-being. Perceived organizational support also positively and significantly enhances employee well-being and represents the strongest direct predictor in the model. Furthermore, employee engagement significantly strengthens the relationships between psychological safety and employee well-being, as well as between perceived organizational support and employee well-being. These findings indicate that supportive and psychologically safe workplaces are more effective in improving well-being when employees are highly engaged. The study contributes to employee well-being literature by providing empirical evidence from an underexplored manufacturing context in Indonesia and offers practical implications for human resource managers.